RESEARCH AND DEVELOPMENT; PENELITIAN DI BIDANG KEPENDIDIKAN YANG INOVATIF, PRODUKTIF DAN BERMAKNA - M. HAVIZ (Ta'dib, 2013)
The focus of this paper is the research and development, as a kind of educational research that is innovative, productive and meaningful. The product of research and development in aspects, especially in education has been able to make the job easier and more enjoyable. Developing of learning as a model, curriculum and component have been able to make learning easier. Example, with the integration of information and communication technology (ICT) into the learning process, making the learning can be done in many places. Research and development can be done with various models that have been developed by experts, such as Plomp, 4-D, and Borg and Gall. The researchers were able to select and adopt it has been developed by expert. The research phase of development should have the design, development and evaluation of the product. Indeed, studies conducted have a positive contribution to the advancement and improvement of the quality of the learning process.Kata kunci:    research and development, education, inovatif, productive, meaningfull